Real time power control strategy for output power for single phase inverter-linear load - Zaidan, Ahmed Naji (2019)
Power electronics have been widely used in many applications due to its reliability in controller. This project is to describe and test the real time power control strategy for output power for inverter-linear load connection. The current control strategy was adapted in controlling the output power of inverter to the resistive load. This was done by controlling the output current of the inverter. The output current was controlled by comparing between desired value with the target reference current. The feedback signal from the current output was processed by the microcontroller through the current sensor. The Texas Instrument C2000 microcontroller was used. The justification of this choice was its ability to convert the signal of the current sensor from analog to digital directly from the microcontroller. The controller used was developed from Proportional integral (PI) controller theory using the MATLAB SIMULINK software. At the end, the output power of the inverter was able to control the output current of the inverter as designed. The results obtained reflects a single phase inverter with a controlled output power at the desired value. This is an indication that the output current of inverter was controlled.